Endzeiten : Eschatologie in den monotheistischen Weltreligionen - Brandes, Wolfram; Schmieder, Felicitas; Brandes, Wolfram; Schmieder, Felicitas (Berlin/Boston De Gruyter, 2008)
In this volume, leading scholars examine the ideas of the last days of the world held in Islam, Christianity and Judaism in the Middle Ages and the Early Modern Age. They discuss the mutual influence of these ideas together with their intended and actual political effect at the time. They open up a significant source for political andintellectual history, because apocalyptic writings are always to be found among the powerful. Key Features: overview of the latest research findings, presented in the form of a handbook successful interdisciplinary dialogue particular focus on the political history and intellectual history of this epoch
German
English
Keywords: Ancient history: to c 500 CE; Classical history / classical civilisation; Medieval history; Comparative religion; Christianity; Islam; Judaism; Eschatology; Middle Ages; Early Modern Age